The clumsy crocodile - Everett, Felicity; Treays, Rebecca De Wolf, Alex (Usborne London, 2002)
When Cassy the clumsy crocodile gets a job at Everglades Department Store, she certainly makes things happen, but not in the way she hopes. Toys, food, china-- she leaves a trail of destruction behind her in every department she visits. But in the end, Cassy's clumsiness saves the day and turns her into a hero